Long-acting reversible contraceptives (LARCs) as harm reduction: a qualitative study exploring views of women with histories of opioid misuse - Stephani L. Stancil; Melissa K. Miller; Alex Duello; Sarah Finocchario-Kessler; Kathy Goggin; Rachel P. Winograd; Emily A. Hurley (BMC, 2021)
Abstract Background The sharp rise in opioid use disorder (OUD) among women coupled with disproportionally high rates of unintended pregnancy have led to a four-fold increase in the number of pregnant women with OUD in the United States over the past decade. Supporting intentional family planning can have multiple health benefits and reduce harms related to OUD but requires a comprehensive understanding of women's perspectives of preventing unintended pregnancies. The purpose of this study was to comprehensively evaluate the knowledge, attitudes and experiences as they relate to seeking contraception, particularly LARCs, among women with active or recovered opioid misuse. Methods In-depth interviews and focus group discussions with 36 women with current or past opioid misuse were recorded and transcribed. Transcripts were coded by ≥ 2 investigators. Themes related to contraceptive care seeking were identified and contextualized within the Health Belief Model. Results Our analysis revealed seven interwoven themes that describe individual level factors associated with contraceptive care seeking in women with current or past opioid misuse: relationship with drugs, reproductive experiences and self-perceptions, sexual partner dynamics, access, awareness of options, healthcare attitudes/experiences, and perceptions of contraception efficacy/ side effects. Overall, perceived susceptibility and severity to unintended pregnancy varied, but most women perceived high benefits of contraception, particularly LARC. However, perceived barriers were too high for most to obtain desired contraception to support family planning intentions. Conclusions The individual-level factors identified should inform the design of integrated services to promote patient-centered contraceptive counseling as a form of harm reduction. Interventions should reduce barriers to contraceptive access, particularly LARCs, and establish counseling strategies that use open, non-judgmental communication, acknowledge the continuum of reproductive needs, explore perceived susceptibility to pregnancy, and utilize peer educators.